Dargon Acemoglu & James A. Robinson, Why Nations Fail: The origins of Power, Prosperity and Poverty - Ms. Farzana Siddique (CISS Insight Journal, 2014)
Why Nations Fail: The Origins of Power, Prosperity and Poverty is an in-depth look at the growing income and wealth disparities between rich and poor countries. The central theme of this book is to explain the concept of inclusive and extractive political and economic systems, which according to the authors are responsible for the disparity of wealth among the countries. Authors have made a comparative analysis of the countries like US, Britain and Germany with the poor countries, such as those in Sub-Saharan Africa, Central America and South Asia. The authors categorize the two sets of countries, the rich and the poor, according to the sociopolitical systems prevailing in each state. Developed countries have an inclusive system and most of the developing countries are practicing extractive political and economic systems.The whole debate in the book revolves around the framework of inclusive political and economic systems and its impact on an economic and political progress of the country whose institutions are practicing these systems. The authors have explained these concepts with the help of analogies and tested their theory on the basis of historical experiences of various states and their current status in the world.